Nanostructured Silicon for Anodes of Lithium-Ion Batteries - LESHOK, A. A.; SASINOVICH, D. A.; BORISENKO, V. E. (PHYSICS, CHEMISTRY AND APPLICATIONS OF NANOSTRUCTURES, 2015)
Nanostructured silicon films have been fabricated on stainless steel by magnetron sputtering of an Al+Si composite target with a subsequent selective etching off the aluminum from the deposited film. They have been used as anodes in prototype Li-ion cells and subjected to cycling lithiation at high current densities. The fabricated films demonstrate an efficient Li accumulation/release during charging/discharging cycles combined with high mechanical durability.